2012
DOI: 10.2478/v10213-012-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Blood Coagulation and Fibrinolytic Disorders in Severe Endometritis-Pyometra Complex in Bitches

Abstract: Twenty bitches with acute endometritis-pyometra complex (EPC) and 20 clinically healthy bitches were examined. The following coagulation parameters were determined in haemostatic evaluations: prothrombin time (PT), activated partial thromboplastin time (aPTT), thrombin time (TT), fibrinogen concentrations (FBG), D-dimer concentrations (D-D), antithrombin activity (AT), and blood platelet counts (PLT). Morphological and biochemical blood parameters were also analysed. Examinations of animals affected by EPC rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…PLT was significantly lower in PG before the OVH, but increased after 15 days. This result of decreased PLT in pyometra bitches was in accordance with the previous studies [5,19] and it was noted that bitches with endometritispyometra were under risk of disseminated intravascular coagulation (DIC), which decreases the PLT, and other coagulation factors and increase the risk of haemorrhage [19] . In another study [20] , it was revealed plasma coagulation factors were decreased in dogs with sepsis but PLT levels were not differed.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…PLT was significantly lower in PG before the OVH, but increased after 15 days. This result of decreased PLT in pyometra bitches was in accordance with the previous studies [5,19] and it was noted that bitches with endometritispyometra were under risk of disseminated intravascular coagulation (DIC), which decreases the PLT, and other coagulation factors and increase the risk of haemorrhage [19] . In another study [20] , it was revealed plasma coagulation factors were decreased in dogs with sepsis but PLT levels were not differed.…”
Section: Discussionsupporting
confidence: 79%
“…Right shift-hypersegmentation of neutrophils is a nonspecific indicator of aging of these cells in circulation [36] and refers to chronicle of the disease like in these two bitches with pyometra (#p22, #p23). Band neutrophils were found higher but not significant before OVH in PG while in other studies significantly higher in pyometra bitches [5,19] . In our study, two segmented neutrophils were found significantly lower in PG before and after OVH.…”
Section: Discussionmentioning
confidence: 67%
“…However, bacterial endotoxins damage the vascular endothelial structure and cause a prothrombin-antithrombin imbalance; this situation could lead to disseminated intravascular coagulation (DIC) and clinical findings may be severe in bitches with endotoxic pyometra. The prognosis of the disease is more important and the surgical approach may carry a high risk of death [18][19][20] . It was determined that gram negative bacteria (three E. coli and one Ps.…”
Section: Discussionmentioning
confidence: 99%
“…PLT levels in PG were lower before OVH, returning to normal levels 15 days after OVH. A low level of PLT has been described in bitches with pyometra (24) and is seen in other acute infections. The presence of DIC may increase the risk of haemorrhage (23).…”
Section: Tab 1 Cbc Results In Cg and Pg Before Ovh And 15 Days Aftementioning
confidence: 95%